NOVEL “ORANG-ORANG PROYEK”: SEJARAH ORDE BARU - Ramis Rauf (Kantor Bahasa Provinsi Gorontalo, 2020)
This study wants to reveal the truth procedures in Ahmad Tohari's novel Orang-Orang Proyek, as a part of an event and a factor in the presence of a new subject. This research would answer the problem: how was the subjectification of Ahmad Tohari in Orang-Orang Proyek novel as truth procedures? This study used the set theory by Alain Badiou. The set theory explained that within a set there were members of